Preparation and characterization of carbon nanotube filled poly (2-hydroxyethylmethacrylate) nanocomposites. (February 2013) - Prashantha, K.; Rashmi, Baralu J.; Lee, J. H.
Poly(2-hydroxyethylmethacrylate) (PHEMA)/multiwalled carbon nanotubes (MWNTs) nanocomposites were prepared by solvent casting using dimethyl formamide (DMF) solvent via sonication process. Effect of addition of MWNTs on the properties of nanocomposites was investigated at different nanofiller contents. Uniform dispersion and distrubution of nanotubes in PHEMA matrix is obtained within the studied composition range. The electrical resistivity, dielectric permittivity and the loss factor of dry PHEMA and PHEMA/MWNT nanocomposites were studied by varying the MWNT concentration in the frequency range of 30 Hz to 1 MHz. The obtained results indicated that the addition MWNTs to PHEMA matrix decreases the electrical resistivity and increases the dielectric constant at low dielectric loss. The thermal properties of the PHEMA/MWNT nanocomposites were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The thermal behavior of these nanocomposites was also compared with PHEMA homopolymer. The glass transition temperature ( Tg ) of PHEMA homopolymer was found to increase with nanotube concentration. Experimental results also demonstrated that the incorporation of the MWNTs into the PHEMA matrix not only enhanced the mechanical property but also increased and the thermal stability of the PHEMA/MWNT nanocomposites increases with increase in MWNT concentration.